Sky Scanners: Using satellite remote sensing to figure out what Earth is like - Dr. V. Basil Hans (International Journal of Satellite Remote Sensing, 2026)
Satellite remote sensing has changed the way we look at, study, and learn about the Earth changing systems. Orbiting sensors take data from many different spectral bands, giving us constant, large-scale information about land, oceans, and the atmosphere. This study discusses the fundamental concepts of satellite remote sensing, including the various types of sensors, methods for data acquisition, and techniques for interpreting images. It talks about important uses like monitoring the environment, figuring out how climate change is affecting agriculture, predicting disasters, and building cities. The incorporation of sophisticated machine learning methods and cloud-based systems has greatly enhanced the efficiency of data processing and the precision of analyses. The focus is on how modern technologies like high-resolution imagery, real-time data processing, and integration with geographic information systems (GIS) have made things more accurate and easier to get to. These technologies facilitate time-series analysis, allowing for the identification of subtle environmental changes over long durations. The article also talks about problems including limited data, interference from the atmosphere, and the necessity for competent analysis. To tackle these problems, correction algorithms and easy-to-use analytical tools have been developed. In the end, satellite remote sensing is a valuable instrument for sustainable development since it helps us make better decisions and learn more about how quickly our planet is changing.
Keywords: Climate Monitoring; Environmental Mapping; GIS Integration; Geospatial Analysis; Satellite Remote Sensing; earth observation